Remarkable therapeutic effects of methylphenidate in periodic limb movement disorder comorbid with excessive daytime sleepiness: a case report - Ren, Jiafeng; Zhang, Xinyan; Zhou, Junying; Liu, Liu (Frontiers in Neuroscience, 2025)
BackgroundPeriodic limb movement disorder (PLMD) is a sleep-related movement disorder, which may be accompanied by a complaint of excessive daytime sleepiness (EDS). With this study, we reported a clinical therapy process up to 2.5 years follow-up, exploring the therapeutic effect of a series of medicines in PLMD comorbid EDS.Case presentationA 27-year-old woman suffered from EDS for more than 10 years and was then diagnosed with PLMD. Initially, we used levodopa 250 mg per night for 12 weeks, then piribedil 50 mg per night was arranged as the second drug for 12 weeks, and the third drug, pramipexole, was prescribed at a dosage of 0.25 mg per night for 12 weeks, but the EDS was persistent despite the periodic leg movement index (PLMI) returning to normal. Finally, methylphenidate was prescribed at a dosage of 18 mg per day after 4 weeks of washout. Then, the indicators of EDS and PLMD all returned to normal after 6 weeks. A 2.5-year follow-up was scheduled for taking methylphenidate; the symptoms of EDS were steadily well controlled, and PLMI was still kept in the normal range.ConclusionThis finding suggests that methylphenidate is an optimal therapeutic approach for the management of PLMD comorbid EDS.